2018
DOI: 10.1055/s-0038-1673700
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Subtype of Poorly Differentiated Invasive Ductal Carcinoma of the Breast Based on Vimentin and E-cadherin Expression

Abstract: Objective The use of molecular markers can identify a subgroup of tumors with distinct recurrence patterns. The present study aimed to characterize the immunohistochemical expression of vimentin (VIM), of E-cadherin (CDH1), and of cytokeratin 5 (CK5) in patients with invasive ductal carcinomas (IDCs). Methods We have constructed a tissue microarray (TMA) from 87 patients with IDC of the breast. Immunohistochemistry (IHC) was performed to study the expression of estrogen and progesterone receptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Another question is whether E-cadherin deletion in tumors causes EMT or a histologically undifferentiated phenotype. In gastric cancer and breast cancer, Cdh1 -deficient tumors often become poorly differentiated tissue 8 , 41 . In the present study, allografts of Cdh1 -deficient and Kras mutational tumors showed a tissue type similar to undifferentiated pancreatic cancer.…”
Section: Discussionsupporting
confidence: 59%
“…Another question is whether E-cadherin deletion in tumors causes EMT or a histologically undifferentiated phenotype. In gastric cancer and breast cancer, Cdh1 -deficient tumors often become poorly differentiated tissue 8 , 41 . In the present study, allografts of Cdh1 -deficient and Kras mutational tumors showed a tissue type similar to undifferentiated pancreatic cancer.…”
Section: Discussionsupporting
confidence: 59%
“…Although some studies have shown that vimentin expression is a marker for poor prognosis [36], others have reported that its high expression can sensitize triple-negative breast cancer in vitro and in vivo to the c-Src inhibitor (dasatinib) [37,38]. Moreover, depletion of vimentin mitigates the c-Src inhibitory effects, suggesting that vimentin plays a role in the regulation of c-Src [38,39].…”
Section: Discussionmentioning
confidence: 99%